Enhanced Tissue Factor Pathway Activity and Fibrin Turnover in the Alveolar Compartment of Patients with Interstitial Lung Disease - Günther, A.; Mosavi, P.; Ruppert, C.; Heinemann, S.; Temmesfeld, B.; Velcovsky, H. G.; Morr, H.; Grimminger, F.; Walmrath, D.; Seeger, W. (Thrombosis and Haemostasis, 2000)
Bronchoalveolar lavage fluids (BALF) from patients with hyper- sensitivity pneumonitis (HP; n = 35), idiopathic pulmonary fibrosis (IPF, n = 41) and sarcoidosis (SARC, n = 48) were investigated for alterations in the alveolar hemostatic balance. Healthy individuals (n = 21) served as Controls. Procoagulant activity (PCA), tissue factor (TF) activity and F VII activity were assessed by means of specific recalcification assays. The overall fibrinolytic activity (FA) was measured using the 125I-labeled fibrin plate assay. Fibrinopeptide A (FP-A), D-Dimer, plasminogen activators (PA) of the urokinase (u-PA) or tissue type (t-PA), PA-Inhibitor I (PAI-1) and α2-antiplasmin (α2-AP) were determined by ELISA technique. As compared to Controls, all groups with interstitial lung disease (ILD) displayed an increase in BALF PCA by approximately one order of magnitude, and this was ascribed to enhanced TF activity by >98%. Accordingly, F VII-activity was increased in all ILD groups, and elevated FP-A levels were noted. There was no significant difference in procoagulant activi- ties between the different ILD entities, but the increase in TF was significantly correlated with deterioration of lung compliance. Overall fibrinolytic activity did not significantly differ between ILD entities and Controls, although some reduction in IPF subjects was observed. Nevertheless, changes in the profile of the different pro- and anti- fibrinolytic compounds were noted. U-PA, but not t-PA levels were significantly reduced in all ILD groups. α2-AP was markedly elevated throughout, whereas PAI-1 levels were lowered. As a balance of enhanced procoagulant and sustained overall fibrinolytic activity, lavage D-dimer levels were elevated by more than one order of magnitude in all ILD patients. We conclude that the predominant alteration in alveolar hemostatic balance in all groups of ILD patients is an enhancement in TF factor pathway activity. Concomitantly, various compounds of the (anti-)fibrinolytic pathways present with altered concentrations, but the overall BALF fibrinolytic activity is largely unchanged. The net enhancement of fibrin turnover is significantly correlated with the decrease in lung compliance.Abbreviations: α2-AP – α2-antiplasmin; ARDS – acute respiratory distress syndrome; BAL – bronchoalveolar lavage; BALF – BAL fluids; BSA – bovine serum albumin; FEV1 – forced expired volume within 1 s; FP-A – fibrinopeptide A; FVC – forced vital capacity; ILD – interstitial lung disease; IPF – idiopathic pulmonary fibrosis; HP – hypersensitivity pneumonitis; PAI-1 – plasminogen-activator-inhibitor-1; PBS – phosphate buffered saline; PCA – procoagulant activity; PL – phospholipid; PPQ – phospholipid-proteinquotient; SARC – sarcoidosis; t-PA – tissue-type plasminogen activator; u-PA – urokinase-type plasminogen activator
Keywords: Tissue factor; PAI-1; u-PA; t-PA; interstitial lung disease (ILD)